Uplink Non-Orthogonal Multiple Access (NOMA) Decoding Based on Successive Parzen Windows Interference Cancellation - Victor P. Gil Jimenez; Angel Navia Vazquez (IEEE Open Journal of Vehicular Technology)
In this paper, a novel decoding kernel method based on Successive Parzen Windows Interference Cancellation (SPWIC) is proposed for the Non-Orthogonal Multiple Access (NOMA) uplink. The procedure leverages on the diversity in both angle and received power at a 3D antenna combined with a Parzen Windows based decoding to achieve better interference cancellation, providing the decoding process with robustness against multi-user interference and user discrimination. This is specially convenient in vehicular scenarios in crowded cities. We have evaluated SPWIC in various scenarios and concluded that it outperforms the standard Successive Interference Cancellation (SIC) approach even in Multiple-Input Multiple-Output (MIMO) cases such that up to 9 users can be allocated on the same resources -as long as they are not too close to each other-. Although it is proposed for mmWave, it can be directly adapted to lower frequencies.